Optical and electrical properties of a spiral LED filament *Project supported by the National Nature Science Foundation of China (No. 51302171), the Science and Technology Commission of Shanghai Municipality (CN) (No. 14500503300), the Shanghai Municipal Alliance Program (No. Lm201547), the Shanghai Cooperative Project (No. ShanghaiCXY-2013-61), and the Jiashan County Technology Program (No. 20141316). (February 2018) - Wang, Liping; Zou, Jun; Yang, Bobo; Li, Wenbo; Li, Yang; Shi, Mingming; Zhu, Wei; Zhang, Canyun; Wang, Fengchao; Lin, Yujie
Abstract: This paper introduces a new type of spiral white light-emitting diodes (WLED) filament with high luminous efficiency and uniform optical performance. The optical and thermal properties of the flexible filament were investigated at different stretching heights, namely 0, 1, 2, and 3 cm. The results indicated that the filament showed the best optical characteristics at the stretching height of 2 cm, because of good heat dissipation. In addition, the radiation temperature of the filament was inversely proportional to the output luminous flux. The reliability of the filament at a stretching height of 2 cm was also evaluated after 1000 h of use. The result demonstrated that the luminous flux decay of the bulb was only 0.85%. The flexible spiral WLED filament exhibiting high luminous flux and good reliability could be adapted to promote industrial development in the near future.